The Effectiveness of Short-Term Counselling in the Treatment of Mass Traumatic Events: A Comparison of Cases Related and Unrelated to COVID-19 - Waterman, Robert W.; Primiano, Sandra; Remers, Shannon (Canadian Journal of Counselling and Psychotherapy, 2025)
A great deal of concern exists over the impact of COVID-19 on people’s mental health, with many employees experiencing anxiety over their health and safety and that of their loved ones. The viability of short-term counselling to treat mental health cases related to COVID-19 was explored. Two hypotheses were tested: 1) the short-term counselling component of employee and family assistance programs is equally effective in the treatment of cases related to COVID-19 as it is in the treatment of cases unrelated to COVID-19; 2) after a certain number of counselling sessions, the improvement in outcomes greatly diminishes for short-term counselling cases. Results showed positive outcomes for both case types, related or not to COVID-19. In addition, a diminishing return was found as the number of treatment sessions increased. From a clinical perspective, the results supported the viability of short-term counselling as a treatment option for cases related to COVID-19, thus suggesting short-term counselling is an effective approach for mental health issues stemming from mass traumatic events.